2005
DOI: 10.1002/app.21502
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of terephthalamides from poly(ethylene terephthalate) waste

Abstract: Poly(ethylene terephthalate) (PET) waste flakes (blow-molded-grade industrial waste) were degraded with aqueous methylamine and ammonia at room temperature in the presence and absence of quaternary ammonium salt as a catalyst for various times. The catalyst reduced the time required for the degradation of the PET waste. The degraded products were analyzed with IR, nuclear magnetic resonance, mass spectrometry, and differential thermal analysis and were characterized as N,NЈ-dimethylterephthalamide and terephth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 12 publications
1
38
0
Order By: Relevance
“…The chemicals such as alkyl amines or liquid ammonia are used in excess for PET de-polymerization (Table 4). Aminolysis and ammonolysis mainly yielded the corresponding monomeric amides of terephthalic acid [223,[226][227][228][229][230][231][232][233][234]. The de-polymerization agent, which was mainly applied, was ethanol amine (EA, Table 4).…”
Section: Aminolysis/ammonolysismentioning
confidence: 99%
See 2 more Smart Citations
“…The chemicals such as alkyl amines or liquid ammonia are used in excess for PET de-polymerization (Table 4). Aminolysis and ammonolysis mainly yielded the corresponding monomeric amides of terephthalic acid [223,[226][227][228][229][230][231][232][233][234]. The de-polymerization agent, which was mainly applied, was ethanol amine (EA, Table 4).…”
Section: Aminolysis/ammonolysismentioning
confidence: 99%
“…Further, but less used chemicals for aminolysis or ammonolysis of PET are methyl amine (MA), liquor ammonia (NH 3 ) and ethylene diamine (EDA). As in case of EA, these chemicals lead to the formation of corresponding bi-functional monomers of terephthalic acid, which could be applied as curing agents for epoxy resins [227,228,233]. Hoang and Dang used excess EDA to depolymerize PET to low molecular weight oligomers (250-820 g·mol -1 , Table 4 ).…”
Section: Aminolysis/ammonolysismentioning
confidence: 99%
See 1 more Smart Citation
“…Soni et al [16] have suggested that aminolysis with 99% hydrogen monohydrate degrades PET bottles, increases percent crystallinity of the residue and decreases molecular weight. Soni and Singh [17] reported the formation of terephthalamide and N,N -dimethyl terephthalamide by the degradation of PET waste through aminolysis and ammonolysis using aqueous methylamine and ammonia, respectively at normal conditions of temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Aminolysis of PET has been carried out using different amines such as allyl amine 3 , alkyl amine 4 , morpholine, hydrazine hydrate 5 , polyamines and triethanolamine 6,7 . Earlier in our laboratory, PET has been depolymerized by ethanolamine using simple chemicals as catalysts such as sodium acetate, glacial acetic acid, potassium sulfate and sodium bicarbonate under reflux with conventional heating for 8 h and under microwave heating for 7 min to get the virtual monomer bis (2-hydroxyethyl) terephthalamide (BHETA) 8,9 with about 86 % yield comparable with that obtained using the conventional lead or zinc acetate catalysts, which are in the category of heavy metals.…”
mentioning
confidence: 99%